ANALISIS SIKAP DAN PENGETAHUAN KONSUMEN TERHADAP ECOLABELLING SERTA PENGARUHNYA PADA KEPUTUSAN PEMBELIAN PRODUK RAMAH LINGKUNGAN - Sumarsono, Sumarsono; Giyatno, Yayat (Faculty of Economics and Business Universitas Jenderal Soedirman, 2012)
The purposes of this study are: 1) To obtain an overview of consumer’s knowledge level of the environmental information on eco-friendly product. 2) To obtain an overview of consumers attitude towards consumption behavior impact on the environment. 3) Knowing the effect of consumer’s knowledge and Consumer attitudes towards the environment on eco-friendly product purchasing decisions. Descriptive qualitative analysis and multiple linier regression analysis used to analyze the data. The results of 80 respondents indicate that 1) the level of consumer’s knowledge on the environmental information on product packing is low. 2) Consumers attitudes towards consumption behavior impact on the environment is positive. 3) There is no positive effect of consumer’s knowledge to ward eco-friendly product purchasing decisions. 4) There is a positive effect of consumer’s attitudes toward eco-friendly product purchasing decisions.